1999
DOI: 10.1590/s0004-282x1999000600002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance findings in amyotrophic lateral sclerosis using a spin echo magnetization transfer sequence: preliminary report

Abstract: -We present the magnetic resonance (MR) findings of five patients with amyotrophic lateral sclerosis (ALS) using a spin-echo sequence with an additional magnetization transfer (MT) pulse on T1-weighted images (T1 SE/MT). These findings were absent in the control group and consisted of hyperintensity of the corticospinal tract. Moreover we discuss the principles and the use of this fast but simple MR technique in the diagnosis of ALS.KEY WORDS: amyotrophic lateral sclerosis, pyramidal / corticospinal tract, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…We consider the centrum semiovale and the precentral subcortical and cortical regions as the best locations to look for CST involvement, because they represent the largest transverse section of the CST in the central nervous system. Some authors demonstrated the value of the T1 SE/MTC sequence to detect CST involvement in ALS patients with high specificity and no false‐positive results 18, 19. Similar results were observed in our MSA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the centrum semiovale and the precentral subcortical and cortical regions as the best locations to look for CST involvement, because they represent the largest transverse section of the CST in the central nervous system. Some authors demonstrated the value of the T1 SE/MTC sequence to detect CST involvement in ALS patients with high specificity and no false‐positive results 18, 19. Similar results were observed in our MSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…In several neurological conditions, the magnetization transfer ratio (MTR) may indicate the presence of structural changes in encephalic tissue, even when signal intensity changes are absent on conventional sequences 16, 17. The T1 spin‐echo with an additional magnetization transfer contrast pulse (T1 SE/MTC) sequence is sensitive and accurate in depicting corticospinal tract (CST) degeneration in amyotrophic lateral sclerosis (ALS), whereas FLAIR imaging was not 18, 19…”
mentioning
confidence: 99%
“…In the search for the diagnostic test, several imaging modalities have been used with varying success: specifically, diffusion tensor imaging (DTI),17–23 magnetization transfer imaging (MTI),24–27 and proton magnetic resonance spectroscopy ( 1 H‐MRS) 23,28–31. In the following sections, we review the current recognized roles of conventional magnetic resonance imaging (MRI), DTI, MTI, and 1 H‐MRS in the diagnosis of ALS and PLS.…”
Section: Diagnosis Of Umn Involvementmentioning
confidence: 99%
“…The findings of a bilateral symmetrical hyper intensity of the pyramidal tract are suggestive of Als denoting degeneration of corticospinal tracts 11,12 . considering the clinical and laboratory findings, the motor neuron diseases have been classified as Als / DNM (sporadic cases, family or genetically determined), Alsplus syndromes (multisystem neurodegenerative disease affecting motor neurons), the Als -related syndromes (represent symptomatic or secondary forms of motor neuron disease, with a known associated condition that may be causing the disease) and the Als -variants (are uncommon unless the patient lives in particular geographic locations) ( Table 9) 13,14 .…”
Section: Diagnosismentioning
confidence: 97%